(3GdcaGjI aj eYQaI GdQhGjIs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH eG LGA ai QhGjI GdMOjK Ydi GddaX hef QCI Pdc hGLHkG s
(3BNQgG (B:s
(3jfJgi GdLRA GdSGHY HBNQ HGH ai GdbGHdI hJUMjM GdcJGH s
(3Ydjg SeGYGJ YOjOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1499s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs